Tracing the real power transfer of individual generators to loads using least squares support vector machine with continuous genetic algorithm - Mohd Wazir, Mustafa, Dr.; Saifulnizam, Abd. Khalid, Dr.; Mohd Herwan, Sulaiman; Siti Rafidah, Abd Rahim; Omar, Aliman; Hussain, Shareef, Dr. (Institute of Electrical and Electronics Engineers (IEEE), 2011)
Link to publisher's homepage at http://ieeexplore.ieee.org/